Electronic Band Structures: Direct Measurement of Electronic Band Structure in Single Quantum Dots of Metal Chalcogenide Composites (Small 51/2018). Issue 51 (20th December 2018) - Benetti, Daniele; Cui, Daling; Zhao, Haiguang; Rosei, Federico; Vomiero, Alberto
Abstract : In article number1801668, Federico Rosei, Alberto Vomiero, and co‐workers use Kelvin probe force microscopy to investigate the electrical properties of individual metal chalcogenide quantum dots (QDs) on a graphene‐like substrate. The electronic properties of individual QDs are measured, minimizing any other collective effect. These results can have an impact on engineering charge dynamics in complex systems, where the motion of photoexcited charges has critical importance.